Optimalisasi Capaian Program Jaminan Kesehatan Nasional (JKN) Berdasarkan Tinjauan Maqasid Syari’ah dan Teori Keadilan Hukum : Studi Kasus Kabupaten Rejang Lebong - Ade Kosasih; David Aprizon Putra; Siti Komsiah Maskurung; Tri Gusti Yanto (University Of Bengkulu Law Journal, 2024)
Health services in Bengkulu Province are still very limited due to the lack of transportation and infrastructure conditions, the number of FKTP (First Level Health Facilities) is still in the category of insufficient, the number of specialist doctors is still very limited, one of which is the case in Rejang Lebong Regency. This is certainly the main problem as well as the root of the problem of the National Health Insurance (JKN) programme services in Rejang Lebong Regency. As an initial finding, there is a legal vacuum in the absence of an umbrella of main laws and regulations at the level of Regional Regulations (Perda). The second is related to legal disharmony, as the existing Regent Regulations have not comprehensively followed the mandate of the regulations above them. This research is an empirical juridical research, aimed at examining and knowing what efforts can be made to strengthen the regional laws and regulations of Rejang Lebong Regency to optimise the achievements of the National Health Insurance (JKN) program based on a review of maqasid sharia and legal justice theory. This research is descriptive analysis, focusing on the analysis of regulations within the scope of the problem theme, trying to harmonise the conditions of JKN service policy regulations that should be established in Rejang Lebong based on the conditions and needs of the Rejang Lebong community. The results of the research found, with a study from 2014 to 2020, found 3 obstacles that inhibit the optimal achievement of the JKN KIS program, the first is the apathy of the community, especially PBI APBN and PBI APBD, the second is the lack of encouragement from stakeholders and interests in socialisation efforts and continuous introduction to the community, the third is that the existing regulations are still experiencing lacunae and disharmony, this is a cause that plays a central role in the failure to optimise the JKN KIS program in Rejang Lebong Regency. Efforts that can be made are to form new local regulations, revise existing Regent Regulations and add Regent Regulations to strengthen local regulations which are the main legal umbrella which certainly prioritises the value of the benefit of the soul (hifz al-nafs) and the benefit of the mind (hifz al-aql).